2009
DOI: 10.1007/s00466-009-0424-1
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Duffy transformation for integrating vertex singularities

Abstract: For an integrand with a 1/r vertex singularity, the Duffy transformation from a triangle (pyramid) to a square (cube) provides an accurate and efficient technique to evaluate the integral. In this paper, we generalize the Duffy transformation to power singularities of the form p(x)/r α , where p is a trivariate polynomial and α > 0 is the strength of the singularity. We use the map (u, v, w) → (x, y, z) : x = u β , y = xv, z = xw, and judiciously choose β to accurately estimate the integral. For α = 1, the Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 63 publications
(78 reference statements)
1
67
0
Order By: Relevance
“…Following [38], we then use a generalized Duffy-trick to integrate each triangle with a proper Gaussrule that respects the order of the singularity depending on the angleˇ˙.…”
mentioning
confidence: 99%
“…Following [38], we then use a generalized Duffy-trick to integrate each triangle with a proper Gaussrule that respects the order of the singularity depending on the angleˇ˙.…”
mentioning
confidence: 99%
“…This scheme has been used for integration of stiffness matrix entries in the X-FEM where the shape function space is enriched with near-tip functions that have singular derivatives [58]. Mousavi and Sukumar [13] presented a generalized form of the Duffy transformation:…”
Section: Generalized Duffy Transformationmentioning
confidence: 99%
“…The Duffy mapping removes the 1/r singularity and the transformed integral is amenable to tensor-product Gauss quadrature. Mousavi and Sukumar [13] have shown that the Duffy transformation is efficient for a 1/r singularity, but is not as efficient for 1/r α singularities when α = 1 (e.g., crack modeling in the X-FEM where α = 1/2 is present). Moreover, for 1 < α < 2 in two dimensions (2 < α < 3 in three dimensions), the Duffy transformation does not remove the singularity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations